Comparing the efficacy of endovascular treatment for iliac vein compression syndrome with or without acute deep venous thrombosis: A single-center retrospective study. (April 2022) - Tu, LK; Nie, ML; Fu, J; Liu, FY; Chen, YK; Sun, JM; Wang, HY
Background: To compare the efficacy of endovascular treatment for iliac vein compression syndrome (IVCS) with or without acute deep venous thrombosis of lower extremity. Methods: This study retrospectively analyzed the clinical data of 300 IVCS patients, who received endovascular treatment between January 2013 and December 2017. According to whether IVCS was complicated by deep venous thrombosis or not, these patients were divided into non-thrombotic iliac vein lesion group (NIVL group, n  = 127) and post-thrombotic iliac vein lesion group (PIVL group, n  = 173). After endovascular treatment, all patients were followed up to assess the symptoms improvement and to evaluate the patency of iliac vein. Results: The technical success rate was 98% (294/300), and percutaneous transluminal angioplasty with stenting was adopted in 294 cases. The incidence of perioperative complications was 36.33% (109/300), but no severe complications occurred. During a mean follow-up of 22.3 months (range 6–30 months), 9(6.82%, 9/132) patients in PIVL group had recurrence of deep venous thrombosis, but nobody had deep venous thrombosis and varicose veins recurrence in NIVL group. The effective rate of endovascular treatment in NIVL group and PIVL group was 96.88% and 90.15% ( P  =   0.050), while the cumulative primary patency of iliac vein in NIVL group was significantly higher than that in PIVL group ( P  =   0.008). Conclusions: The endovascular treatment is an effective, feasible, safe method for treating IVCS. There is no difference in the efficacy of IVCS patients with or without deep venous thrombosis, but the medium and long-term patency of patients with deep venous thrombosis is lower than that in patients without deep venous thrombosis.